Thermal stability of titanium hydride modified by the electrochemical deposition of titanium metal - R N Yastrebinsky; V I Pavlenko; A A Karnauhov; N I Cherkashina; A V Yastrebinskaya (Materials Research Express, 2020)
This study aims to address the poor thermal stability of titanium hydride. Surface microstructural observations, differential thermal analysis, and electron-probe analysis of the thermal stability and phase composition measurements of a titanium hydride fraction that was modified by the electrochemical deposition of titanium metal are presented. It is demonstrated that the metallic titanium deposited on the surface of the fraction acts as an effective trap for hydrogen diffusion into the surface layers upon thermal heating. Modification of the surface of the titanium hydride fraction by electrochemical deposition of titanium metal increased its initial temperature of dehydrogenation by 231.8 °C. The concentration of the hydride phase at the surface layer at 500 °C increased to 87.2% due to the structural redistribution of atomic hydrogen and the hydrogenation of metallic titanium at the surface layer.